10 000 Consecutive off Pump Coronary Artery Bypass Grafting Operations Performed in a Single Cardiac Surgery Clinic - Rudenko, A. V.; Ursulenko, V. I.; Kupchynskiy, A. V.; Spysarenko, S. P.; Malysheva, T. A. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The work summarizes the results of more than 10 000 consecutive off pump coronary artery bypass grafting operations performed in a single cardiac surgery center. The immediate results of these operations, the causes of postoperative complications were analyzed on extensive statistical material.